Non‐bismuth and bismuth quadruple therapies based on previous clarithromycin exposure are as effective and safe in an area of high clarithromycin resistance: A real‐life study. Issue 4 (20th April 2020) - Romano, Marco; Gravina, Antonietta Gerarda; Nardone, Gerardo; Federico, Alessandro; Dallio, Marcello; Martorano, Marco; Mucherino, Caterina; Romiti, Alessandra; Avallone, Luciana; Granata, Lucia; Priadko, Katerina; Compare, Debora; et al.
Abstract: Background: Bismuth quadruple (BQT) and non‐bismuth quadruple (N‐BQT) therapies are the recommended first‐line treatments for Helicobacter (H.) pylori infection. Objective: To compare the efficacy of BQT and N‐BQT in clinical practice in an area with high clarithromycin resistance, choosing the regimen on the basis of previous exposure to clarithromycin. Methods: A total of 404 consecutive H pylori ‐positive, naïve patients were enrolled. A total of 203 patients without previous exposure to clarithromycin received N‐BQT, 100 patients for 10 days and 103 for 14 days, whereas 201 with previous exposure to clarithromycin received 10‐day BQT. Efficacy and treatment‐related adverse events were assessed. Results and Conclusions: Eradication rates by intention‐to‐treat analysis were 88.2% for N‐BQT and 91.5% for BQT ( P = .26); per‐protocol analysis eradication rates were 91.2% and 95.8% for N‐BQT and BQT, respectively ( P = .07). Eradication rates were significantly higher with 14‐day than 10‐day CT ( P < .003). Almost all patients had a good compliance with both N‐BQT (95.6%) and BQT (95%). Adverse events occurred in 24.1% and 26.9% ( P = .53) of patients in the N‐BQT and BQT group, respectively. In conclusion, clarithromycin‐containing non‐bismuth or bismuth quadruple therapy, based on the knowledge of previous clarithromycin exposure, is effective and safe even in an area of high prevalence of clarithromycin‐resistant H pylori strains.